Turning Noise Into Data: Characterization of the Van Allen Radiation Belt Using SDO Spikes Data - Spiridon Kasapis; Barbara J. Thompson; Juan V. Rodriguez; Raphael Attie; Gonzalo Cucho‐Padin; Daniel daSilva; Meng Jin; William D. Pesnell (Space Weather)
Abstract The Solar Dynamics Observatory (SDO) is a solar mission in an inclined geosynchronous orbit. Since commissioning, images acquired by Atmospheric Imaging Assembly (AIA) instrument on‐board the SDO have frequently displayed “spikes,” pixel regions yielding extreme number of digital counts. These are theorized to occur from energetic electron collisions with the instrument detector system. These spikes are regularly removed from AIA Level 1.0 images to produce clean and reliable data. A study of historical data has found over 100 trillion spikes in the past decade. This project correlates spike detection frequency with radiation environment parameters in order to generate an augmented data product from SDO. We conduct a correlation study between SDO/AIA data and radiation belt activity within the SDO's orbit. By extracting radiation “spike” data from the SDO/AIA images, we produce a comprehensive data product which is correlated not only with geomagnetic parameters such as Kp, Ap, and Sym‐H but also with the electron and proton fluxes measured by the GOES‐14 satellite. As a result, we find that AIA spikes are highly correlated with the GOES‐14 electrons detected by the magnetospheric electron detector and energetic proton, electron and alpha detectors instruments at the equator (where the two satellites meet) with Spearman's Correlation values of ρ = 0.73 and ρ = 0.53, respectively, while a weaker correlation of ρ = 0.47 is shown with magnetospheric proton detector protons for the 2 year period where both missions returned data uninterruptedly. This correlation proves that the SDO spike data can be proven useful for characterizing the Van Allen radiation belt, especially at areas where other satellites cannot.